2018
DOI: 10.1038/s41467-018-02933-6
|View full text |Cite
|
Sign up to set email alerts
|

Selective control of fcc and hcp crystal structures in Au–Ru solid-solution alloy nanoparticles

Abstract: Binary solid-solution alloys generally adopt one of three principal crystal lattices—body-centred cubic (bcc), hexagonal close-packed (hcp) or face-centred cubic (fcc) structures—in which the structure is dominated by constituent elements and compositions. Therefore, it is a significant challenge to selectively control the crystal structure in alloys with a certain composition. Here, we propose an approach for the selective control of the crystal structure in solid-solution alloys by using a chemical reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
98
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 38 publications
(29 reference statements)
0
98
0
Order By: Relevance
“…Organic compounds such as alcohols, polyalcohols (polyols), and phenols are attractive for the synthesis of colloidal metal nanocrystals as they can play multiple roles in a reaction, acting as a solvent, and/or stabilizer, in addition to a reductant . Among various alcohols, methanol and ethanol are the most commonly used because of their abundance and relatively lower prices than other alcohols such as n‐propanol, n‐butanol, and 1‐hexanol . In general, primary alcohols always work as reductants due to their superior reactivity relative to secondary and tertiary alcohols.…”
Section: Case Studiesmentioning
confidence: 99%
“…Organic compounds such as alcohols, polyalcohols (polyols), and phenols are attractive for the synthesis of colloidal metal nanocrystals as they can play multiple roles in a reaction, acting as a solvent, and/or stabilizer, in addition to a reductant . Among various alcohols, methanol and ethanol are the most commonly used because of their abundance and relatively lower prices than other alcohols such as n‐propanol, n‐butanol, and 1‐hexanol . In general, primary alcohols always work as reductants due to their superior reactivity relative to secondary and tertiary alcohols.…”
Section: Case Studiesmentioning
confidence: 99%
“…The first example of crystal structure control in a binary alloy by using a chemical reduction method was reported in 2018 in the Au‐Ru system . The proposed strategy was as follows: the crystal structure of binary alloy NPs is dominated by the nuclei structure.…”
Section: Binary Solid‐solution Nanoparticles (Ssnps) Between Immiscibmentioning
confidence: 99%
“…When monitored by UV/Vis, we found that RuCl 3 is reduced earlier than HAuBr 4 for the synthesis of hcp‐AuRu 3 NPs (Figure d, e). By using the CV method, we further found that the reduction potential of [AuBr 4 ] − with CTAB was lower than that without CTAB (0.768 vs. 0.856 V), which can be explained by the formation of a complex between [AuBr 4 ] − and CTAB …”
Section: Binary Solid‐solution Nanoparticles (Ssnps) Between Immiscibmentioning
confidence: 99%
“…As one of the most common shape-directing agents, the cationic surfactant CTAB has always been a widely utilized in the synthesis of functional materials. 40,41 Fig. S5a and S5b † show the results of the same amount of CTAB were respectively added in DMF and toluene.…”
Section: Roles Of Ctab For the Formation Of Shale-like Cs 4 Pbbr 6 MImentioning
confidence: 99%
“…Cs + , Pb 2+ , Br À ) and CTAB will be recrystallized together due to the increase of toluene content in the reaction solution. Furthermore, it is well known that (i) CTAB can be facilely self- assembled to form layered micelles when its concentration in a solution is higher than the critical concentration 40,41 and (ii) the Gibbs free energy of heterogeneous nucleation is generally lower than that of homogeneous nucleation. 42,43 On the basis of the above information and our experimental results, we infer that, under a slow crystallization process like our case, the layered structure CTAB micelles may act as the so templates and in turn direct the growth process of cesium lead bromide compound, thus leading to the formation of shale-like Cs 4 PbBr 6 microplates.…”
Section: Roles Of Ctab For the Formation Of Shale-like Cs 4 Pbbr 6 MImentioning
confidence: 99%